Marketing in the Network Economy - Achrol, Ravi S.; Kotler, Philip (Journal of Marketing, 1999)
As the twenty-first century dawns, marketing is poised for revolutionary changes in its organizational context, as well as in its relationship with customers. Driven by a dynamic and knowledge-rich environment, the hierarchical organizations of the twentieth century are disaggregating into a variety of network forms, including internal networks, vertical networks, intermarket networks , and opportunity networks. The role of marketing in each network is changing in profound ways. Marketing increasingly will be responsible for creating and managing new marketing knowledge, education, real-time market information systems, intrafirm integration, conflict resolution, technology forecasting, risk and investment analysis, transfer pricing of tangibles and intangibles, and the coordination of the network's economic and social activities. It will explore new frontiers in multilateral marketing, reshape markets through technology convergence and electronic commerce, organize consumer communities, and aggregate consumer information and demand into saleable business assets. The most radical implication for marketing is the shift from being an agent of the seller to being an agent of the buyer, from being a marketer of goods and services to being a customer consultant and manager of his or her saleable consumption assets.